K-Punk - Fisher, Mark 1968-2017; Ambrose, Darren; Reynolds, Simon 1963- (London Repeater, 2018)
This comprehensive collection brings together the work of acclaimed blogger, writer, political activist and lecturer Mark Fisher (aka k-punk). Covering the period 2004 - 2016, the collection will include some of the best writings from his seminal blog k-punk; a selection of his brilliantly insightful film, television and music reviews; his key writings on politics, activism, precarity, hauntology, mental health and popular modernism for numerous websites and magazines; his final unfinished introduction to his planned work on "Acid Communism"; and a number of important interviews from the last decade.
The Collected and Unpublished Writings of Mark Fisher (2004-2016)
Keywords: 21st Century (2001-2100); Literature; Philosophy; Esthetics; Music criticism; United Kingdom